The Development of Children's Environmental Identity Through a Descriptive Phenomenological Perspective - Ikra Mulyadi, Veri (Journal of Islamic Elementary Education, 2023)
Modernization and urbanization have brought significant changes to children's living environments, often impacting the development of their environmental identity. The loss of green spaces, urban sprawl, and cultural shifts have reduced children's emotional connection to their residential environments. This study employs a descriptive phenomenological approach to explore children’s subjective experiences in interpreting their environment amidst modernization challenges. Data were collected through in-depth interviews, participatory observations, and narrative analysis to uncover the essence of children’s experiences with physical and social environments. The findings reveal that children’s environmental identity is influenced by physical factors, such asgreen spaces and play facilities, as well as social factors, such as family and community support. Additionally, children’s interaction with digital spaces shapes their perception of the real environment. This research offers recommendations for educators, urban planners, and policymakers to create environments that holistically support the development of children's environmental identity, especially in the context of rapid urbanization.